Um arte-educador no ensino não-formal: um estudo dos sentidos e significados constituídos para a atividade docente de Arte e Cultura em medida socioeducativa - Silva, Vanessa Cristina da (2012)
The present study intended to grasp the senses and meanings that an art educator elaborated to his professional activity, which is the teaching of Art and Culture to adolescents in conflict with law and isolated from society. The research had a qualitative nature and was based on theoretical and methodological assumptions of the socio-historical Psychology. The subject was an art educator who has been teaching street dancing for more than 15 years, despite de fact that he didn t attend higher education. The categories of analysis selected from the theoretical framework were those of senses and meanings, following the methodological approach suggested by Aguiar and Ozella (2006): the construction and analysis of nuclei of meanings. The interpretative and constructive analytical effort showed that the senses and meanings attributed by the participant to his teaching activities were impregnated by his subjectivity, a personal construction based on his individual experience in everyday life. The denial of the role of theory and the excessive emphasis on practice led the subject to immediate, automatic or unthinking actions. It was inferred that the activities of art and culture have an important place in the life of youngsters deprived of freedom, but if such activities are to have an educational nature, teacher training must promote reflection and theorization. In fact, teachers training requires both intellectual and empirical activities, enabling praxis, i. e., theory leading practice and practice placing new questions in the theory. It is only then that is possible to build a teaching process both critical and reflexive, reducing the impact of individual experiences and imposing certain rationality. Teacher's training is the primary way to create educators who act critically, analyzing their doings, their students and their classrooms away from common sense, pragmatism and idiosyncratic meanings formulated exclusively in accordance to their private experience